SOCIO-PSYCHOLOGICAL BASIS FOR DEVELOPING ANTI-CORRUPTION BEHAVIOR FOR STUDENTS (Academia Science Repository, 2023)
Corruption is a major problem in many societies around the world and is one of the main obstacles to progress and progress. Corruption has a negative impact on economic growth, governance, social justice, and society's trust in institutions. In this context, it is very important to develop effective anti-corruption strategies, including conducting educational and community outreach companies. One of the important aspects in this regard is the socio-psychological foundations of the formation of anti-corruption behavior in students. This article is aimed at studying the theoretical foundations and practical consequences of this topic.